INCIDENTAL FINDINGS OF PARANASAL SINUSES IDENTIFIED ON COMPUTER TOMOGRAPHY SCANS - Klagiša, Renāta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The research work has been dedicated for computer tomography and devoted to the analysis of computer tomography scans. Visual diagnostic methods are widely applied in medicine. Therefore incidental findings are more often. An incidental finding is any abnormality not related to the illness or causes that prompted the diagnostic imaging test. Abnormalities of the paranasal sinuses are frequently encountered as incidental findings during spiral computer tomography evaluation of head and cone beam computer tomography for dental purposes. The growing number of imaging techniques performed per patient causes an increase in the number of incidental findings. How these findings should be managed is far from settled.The aim of this study was to retrospectively analyze the occurrence and type of incidental abnormalities of paranasal sinuses detected by radiographic examinations in the Latvian population of adults.The research work includes retrospective data of three hundred patients. They underwent spiral computer tomography scan of the head referred for non-sinus pathologies in Pauls Stradins Clinical University Hospital in Latvia between February 2015 and October 2015.This is the first report describing incidental findings of paranasal sinuses, the types, the most frequently affected sinuses in Latvian population of adults and also associations between incidental findings and such factors as age, gender, season, septal deviation and enlarged inferior nasal turbinates.